Examen especial de propiedad plata y equipo, componente vehículos de la empresa estudiar S.A del periodo 2021. - Alvarado Armijos, Anggie Anabel (Machala : Universidad Técnica de Machala, 2022)
The main objective of this work is to analyze the functions and importance of internal audit and control, from the financial approach, through a bibliographic research, taking into account that for organizations, internal audit and control are tools of great relevance for the executive part, likewise, the application of the special audit examination with their respective adjustments of the vehicle assets of the company ESTUDIAR S.A period 2021 is proposed; same that will allow to determine the shortcomings that the company carries and at the same time to obtain and present possible solutions, same that benefit the organizational growth
El presente trabajo tiene por objetivo principal analizar las funciones e importancia de la auditoría y control interno, desde el enfoque financiero, mediante una investigación bibliográfica, tomando en cuenta que para las organizaciones la auditoría y control interno son herramientas de gran relevancia para la parte ejecutiva, asimismo, se plantea la aplicación del examen especial de auditoría con sus respectivos ajustes del activo vehículo de la empresa ESTUDIAR S.A periodo 2021; mismo que permitirá determinar las falencias que acarrea la empresa y al mismo obtener y presentar posibles soluciones, misma que benefician al crecimiento organizacional
Keywords: CONTROL INTERNO; EXAMEN ESPECIAL; VEHÍCULO; DEPRECIACIÓN